USING AUTHENTIC MATERIALS TO ENHANCE LANGUAGE LEARNING: BENEFITS AND PRACTICAL CONSIDERATIONS - Dja'far, Veri Hardinansyah (Transpublika Publisher, 2022)
The use of authentic materials has long been recognized as a valuable approach in language teaching and learning. This method not only aids in the development of learners' language skills but also helps them apply these skills to real-world situations, thereby enhancing their overall communicative competence. Incorporating authentic texts and tasks fosters an engaging and motivating learning environment, allowing learners to connect with the language in a meaningful way and improve both their autonomy and communicative ability. Moreover, the design of authentic materials can bridge the gap between theory and practice in language education by providing learners with motivating and relevant tasks that align with real-life applications, thereby enriching their overall learning experience. The present study aims to examine the benefits and practical considerations of using authentic materials to enhance language learning. This study is conducted at a junior high school in Central Java, Indonesia, which has been using authentic materials in English Learning. The study reveals that the teacher and the students feel that authentic material is helpful to be applied in classroom learning.